2020
DOI: 10.3390/jcm9103273
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year in-Hospital Mortality Trends among Paediatric Injured Patients in Japan: A Nationwide Observational Study

Abstract: Injury is a major cause of worldwide child mortality. This retrospective nationwide study aimed to evaluate the characteristics of paediatric injured patients in Japan and their in-hospital mortality trends from 2009 to 2018. Injured patients aged <17 years were enrolled. Data were extracted from the Japan Trauma Data Bank. In the Cochran-Armitage test, in-hospital mortality significantly decreased during the study period (p < 0.001), except among patients <1 year old, and yearly reductions were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Therefore, analyses using this database can provide useful evidence for prevention of injury. Two previous reports used the JTDB for investigating child injuries [25,26]. One of these studies focused on child injuries due to MVCs and described the injury patterns and outcomes relating to the seating position of the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, analyses using this database can provide useful evidence for prevention of injury. Two previous reports used the JTDB for investigating child injuries [25,26]. One of these studies focused on child injuries due to MVCs and described the injury patterns and outcomes relating to the seating position of the vehicle.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences in the mortality risk of injured patients according to the severity of anatomical injury. Previous studies have shown that the mortality of injured patients with ISS ≥16 has been decreasing to below 20% [ 9 11 , 13 ]. This study also showed that the mortality rate of injured patients with ISS 0–15 and 16–25 in 2018 was 20% or less, regardless of age, injury mechanism, and injury region.…”
Section: Discussionmentioning
confidence: 99%
“…In patients aged younger than 15 years, the mortality trend in injured patients with ISS ≥26 did not significantly improve, and the in-hospital mortality risk of patient aged 0−4 years with ISS ≥26 remained high during the 10 years of study (26.1%−58.3%). Previous studies suggested that injured patients younger than 5 years had a higher mortality risk, because they included a high proportion of severe head injuries [ 11 , 15 ]. Our results also showed that the OR for mortality in patients with head injury and AIS ≥3 was 3.48.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations